Influence of Pool Detergents on Formation of Chloramines in Swimming Pool Water - Stańkowska, Emilia; Włodyka-Bergier, Agnieszka; Bergier, Tomasz (Geomatics and Environmental Engineering, 2019)
Cleaning agents used in swimming pools are essential elements in maintaining the proper hygiene of a swimming pool facility. They can also pollute water and cause a potential health hazard for swimming pool users. Studies show that the combination of substances used for disinfection with some contaminations presented in pool water can cause the formation of many dangerous by-products. One of these is chloramines, which have carcinogenic and mutagenic properties; this is why an analysis of the factors that influence their formation is very important. The purpose of this article is to determine the effect of pool detergents used on swimming pools on the formation of chloramines in pool water. Samples of swimming pool water were treated with selected detergents (Benamin AKR, Benamin SND, Randklar A, and Randklar S) used in one of Krakow´s public swimming pools and then tested for monochloramine, dichloramine, and trichloride. The results may be helpful in taking the steps to mitigate the negative effects of using cleaning agents.